2021
DOI: 10.1177/23094990211061209
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body mass index on blood loss and complications in simultaneous bilateral total hip arthroplasty: A multicenter retrospective study

Abstract: Background The effect of body mass index (BMI) on blood loss in simultaneous bilateral total hip arthroplasty (SBTHA) was still undetermined. The purpose of the study was to evaluate the blood loss, transfusion and incidence of complications in normal, overweight, and obese patients undergoing SBTHA. Methods A total of 344 patients following SBTHA were enrolled into this study. The patients were assigned into three groups on the basis of their BMI, including normal (BMI 18.0–24.9 kg/ [Formula: see text]), over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…In fact, there are several current publications concerning BMI, blood loss and perioperative transfusions in orthopeadic surgeries. Presented studies do advocate for lower transfusion rates in obese and overweight patients [21][22][23][24]. Thus, our results of lower blood transfusion requirements in the group with the highest BMI align with these previous ndings.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, there are several current publications concerning BMI, blood loss and perioperative transfusions in orthopeadic surgeries. Presented studies do advocate for lower transfusion rates in obese and overweight patients [21][22][23][24]. Thus, our results of lower blood transfusion requirements in the group with the highest BMI align with these previous ndings.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the common assumption of higher intraoperative blood loss and blood transfusion rates in obese patients [35], our study illustrated that blood transfusion requirements tended to be higher among patients with BMI <25 as compared to BMI >30 kg/m 2 . Similar findings were observed in several orthopaedic and cardiothoracic surgeries [36,37], which could be explained by a possibly higher initial blood volume among patients with higher BMI. Finally, our study demonstrated no significant impact of BMI on the conversion rate to open surgery.…”
Section: Discussionsupporting
confidence: 86%
“…Perhaps this is due to higher rates of CHF, pneumonia, and transfusion in non-obese patients during the first 90 days. Previous studies have found reduced mortality from CHF and pneumonia and decreased need for transfusion [ 17 , 24 , 25 ]. This decrease in mortality could reduce the amount of healthcare intervention required and, therefore, reduce the associated healthcare costs.…”
Section: Discussionmentioning
confidence: 99%